Dampak Kenaikan BBM Tahun 2022 Terhadap Pedagang Sembako di Pasar Besar Palangka Raya - Intan Permatasari, Hildha; Muhammad Noor Sayuti; Akhmad Jaki (Islamic Economics and Business Review, 2024)
Abstract The unavoidable increase in prices of various commodities is one of the impacts of the increase in transportation costs which of course follows developments in fuel price increases. This research aims to examine the impact of government intervention in increasing fuel prices on the increase in basic food prices in traditional markets, especially a description of the impact from the traders' side. This research method is qualitative. Type of field research, with a contextual approach to sharia economics. This research uses observation, interviews, and documentation as data collection techniques. The results of this research can be concluded that the increase in fuel prices in 2022 will have a negative impact on basic food traders at Pasar Besar Palangka Raya. The traders' response regarding the 2022 fuel price increase for basic necessities at Pasar Besar Palangka Raya is that basic food traders feel the impact of the fuel price increase and the average number of buyers has decreased after the fuel increase. In terms of elasticity, the demand response includes elastic demand, while the supply response includes inelastic supply. In terms of Islamic economics, the intervention carried out by the government by making a policy to increase fuel prices can be said to be appropriate, but it is still not the price elasticity response that occurs. Keywords: impact; increase in fuel oil; traders in nine basic commodities   Abstrak Kenaikan harga berbagai komoditas yang tidak dapat dihindari menjadi salah satu dampak kenaikan biaya transportasi yang sudah tentu mengikuti perkembangan kenaikan harga BBM. Penelitian ini bertujuan untuk mengkaji dampak intervensi pemerintah dalam menaikkan harga BBM pada kenaikan harga sembako di pasar tradisional, khususnya deskripsi dampak dari sisi pedagang. Metode penelitian ini adalah kualitatif. Jenis penelitian lapangan (field research), dengan pendekatan kontekstual ekonomi syariah. Penelitian ini menggunakan observasi, wawancara, dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian ini dapat disimpulkan bahwa kenaikan harga BBM tahun 2022 berdampak negatif terhadap pedagang sembako di Pasar Besar Palangka Raya. Adapun respon pedagang mengenai kenaikan harga BBM tahun 2022 terhadap sembako di Pasar Besar Palangka Raya adalah pedagang sembako merasakan pengaruh dari kenaikan BBM dan jumlah pembeli yang rata-rata menurun setelah kenaikan BBM. Secara elastisitas, respon permintaan termasuk permintaan elastis, sedangkan respon penawaran termasuk penawaran inelastis. Secara ekonomi Islam, intervensi yang dilakukan pemerintah dengan membuat kebijakan menaikkan harga BBM dapat dikatakan sudah sesuai, namun masih belum pada respon elastisitas harga yang terjadi. Kata kunci: dampak; kenaikan BBM; pedagang sembako